Appropriate Use of Antihypertensive Medicines in Hypertension Patients of BPJS Participants - Ika Pratiwi; Elvira Rosa; Nurul Syazwani; Agustina Kartikasari (CV. Global Health Science Group, 2021)
Hypertension is a health disorder that is often encountered and includes public health that needs to be addressed immediately. Hypertension is a condition in which the blood pressure, either systolic or diastolic, is 140/90 mmHg. WHO (World Health Organization) data shows that there are around 1 billion people with hypertension worldwide. The prevalence of hypertension is predicted to continue to increase, by 2025 it is predicted that as many as 29% of adults have hypertension worldwide. Around 8 million people with hypertension die each year, of which 1.5 million deaths occur in Southeast Asia. This research is a descriptive research. Descriptive research method is a research method that is carried out with the main aim of making a picture or description of a situation objectively. Descriptive research methods are used to solve or answer the problems being faced in the current situation. The profile of the use of antihypertensive drugs in terms of gender is mostly women with a percentage of 57.7%, most patients are in the age group 40-60 years as much as 50.0%. The highest use of single antihypertensive drugs is sulfonylurea 33.6%, combination therapy mostly uses 3 drug classes by 63.6%, namely Alpha Glucoside Inhibitors, Sulfonylureas and Biguanides. For the administration of combination therapy, the most vasodilators are combinations of long- -acting andvasodilators rapidacting 85.7%. Evaluation of the use of antihypertensive drugs in patients with HYPERTENSION BPJS participants in the Outpatient Installation of RSUD Dr. H. Soewondo during 2021 according to Fornas BPJS showed that 91.33% or 274 drug items were written in accordance with National Fornas and 8.67% or 26 drug items were not appropriate.